Low-energy enhancement and fluctuations of γ-ray strength functions in 56, 57Fe: test of the Brink–Axel hypothesis. (24th April 2017) - Larsen, A C; Guttormsen, M; Blasi, N; Bracco, A; Camera, F; Campo, L Crespo; Eriksen, T K; Görgen, A; Hagen, T W; Ingeberg, V W; Kheswa, B V; Leoni, S; et al.
Abstract: Nuclear level densities and γ -ray strength functions of 56, 57 Fe have been extracted from proton- γ coincidences. A low-energy enhancement in the γ -ray strength functions up to a factor of 30 over common theoretical E1 models is confirmed. Angular distributions of the low-energy enhancement in 57 Fe indicate its dipole nature, in agreement with findings for 56 Fe. The high statistics and the excellent energy resolution of the large-volume LaBr3 (Ce) detectors allowed for a thorough analysis of γ strength as function of excitation energy. Taking into account the presence of strong Porter–Thomas fluctuations, there is no indication of any significant excitation energy dependence in the γ -ray strength function, in support of the generalized Brink–Axel hypothesis.